2010
DOI: 10.3945/ajcn.2010.29905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concord grape juice on ambulatory blood pressure in prehypertension and stage 1 hypertension

Abstract: We observed no effect of grape juice on ambulatory blood pressure in this cohort of relatively healthy individuals with modestly elevated blood pressure. Secondary analyses suggested favorable effects on nocturnal dip and glucose homeostasis that may merit further investigation. This trial was registered at clinicaltrials.gov as NCT00302809.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 36 publications
3
73
2
2
Order By: Relevance
“…However, consumption of grape juice for 8 weeks by human subjects with pre-hypertension or Stage 1 hypertension, did not experience lowering of BP (Dohadwala et al, 2010) whereas an 8 week study of grape juice consumption by Korean hypertensive men indicated favourable lowering of BP (Park, Kim, & Kang, 2004). These results may suggest that as proposed for tea (Dong et al, 2011), process-mediated enrichment of the efficacious fraction may be required for demonstrable in vivo effect.…”
Section: Ace Regulation By Dietary Plantscontrasting
confidence: 46%
“…However, consumption of grape juice for 8 weeks by human subjects with pre-hypertension or Stage 1 hypertension, did not experience lowering of BP (Dohadwala et al, 2010) whereas an 8 week study of grape juice consumption by Korean hypertensive men indicated favourable lowering of BP (Park, Kim, & Kang, 2004). These results may suggest that as proposed for tea (Dong et al, 2011), process-mediated enrichment of the efficacious fraction may be required for demonstrable in vivo effect.…”
Section: Ace Regulation By Dietary Plantscontrasting
confidence: 46%
“…Seven trials [14], [17], [21], [25], [24], [29], [30] were classified as high quality (Jadad score ≥4) and the remaining 12 trials were low quality (Jadad score <4). All 7 high-quality trials had adequate allocation concealment (i.e., conducted by a third-party manufacturer or using opaque envelopes) and 2 high-quality trials reported the generation of random numbers or randomization list.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, red wine with and without alcohol decreased both DBP and SBP in clinical studies conducted on a population at high cardiovascular risk (Chiva-Blanch et al, 2012), while consumption of grape polyphenol powder significantly reduced only SBP (Barona et al, 2012). Resveratrol (10 mg) consumed by subjects with a history of cardiovascular disease significantly improved left ventricular diastolic pressure (Magyar et al, 2012), but recent studies that included subjects with prehypertension and mild hypertension showed that the consumption of red wine polyphenols, grape juice or grape seed extract had no effect on BP (Botden et al, 2012;Dohadwala et al, 2010;Ras et al, 2013).…”
Section: Discussionmentioning
confidence: 95%